Investigation on ultrasonic welding attributes of novel carbon/elium® composites - Bhudolia, Somen Kumar (2021)
Joining large and complex polymer-matrix composite structures is becoming increasingly important in industries such as automobiles, aerospace, sports, wind turbines, and others. Ultrasonic welding is an ultra-fast joining process and also provides excellent joint quality as a cost-effective alternative to other joining processes. This research aims at investigating the welding characteristics of novel methyl methacrylate Elium®, a liquid thermoplastic resin. Elium® is the first of its kind of thermoplastic resin, which is curable at room temperature and is suitable for mass production processes. The welding characteristics of Elium® composites were investigated by optimizing the welding parameters with specially designed integrated energy directors (ED) and manufactured using the Resin transfer molding process. The results showed a 23% higher lap shear strength for ultrasonically welded composite joints when compared to the adhesively bonded joints. The optimized welding time for the ultrasonic welded joint was found to be 1.5 s whereas it was 10 min for the adhesively bonded joint. Fractographic analysis showed the significant plastic deformation and shear cusps formation on the fractured surface, which are typical characteristics for strong interfacial bonding.